Polish Independent Press Summary, no. 9 (1987) - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
A digest of Polish underground press (including articles, tables of content, and book covers) compiled by members of the RFE Polish Underground Publications Unit to be used in a daily 20-minute broadcast on Polish samizdat. Extract from Przegląd Wiadmości Agencyjnych, no. 37 (28 October 1987). Extract from Przegląd Wiadmości Agencyjnych, no. 38 (4 November 1987). Extract from Przegląd Wiadmości Agencyjnych, no. 39 (11 November 1987). Extract from KOS, no. 124 (27 September 1987). Extract from Wola, no. 233 (19 October 1987). Extract from Robotnik Wybrzeża Zachodniego, no. 18 (18-30 September 1987). Extract from Serwis Informacyjny Społecznego Komitetu Nauki, no. 53 (4 October 1987). Extract from Dezerter, no. 3(49) (25 October 1987). Table of Contents from Nowa Koalicja, no. 3 (1987). Extract from Nowa Koalicja, no. 3 (1987). Table of Contents from Most - Wolne Pismo, no. 14/15 (1987). Extract from Most - Wolne Pismo, no. 14/15 (1987). Table of Contents from Wezwanie, no. 12 (March 1987). Table of Contents from List of Underground Book Publications received by RFE (May 1986-January 1987)